2020
DOI: 10.1186/s12888-020-02690-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of possible idiopathic normal pressure hydrocephalus in older inpatients with schizophrenia: a replication study

Abstract: Background: We recently reported that older patients with schizophrenia (SZ) show possible idiopathic normal pressure hydrocephalus (iNPH) more frequently than the general population. In this study, we estimated the prevalence of iNPH in a larger number of older SZ patients and explored useful examination values for diagnosis in the SZ population. Methods: We enrolled older inpatients with SZ (n = 39, mean age = 68.6 ± 7.7 years) from several psychiatric hospitals in Ehime, Japan and acquired brain imaging dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…A widely accepted consensus posits that the enlargement of brain ventricles in iNPH is associated with compromised CSF homeostasis (Wang et al, 2020). Additionally, previous studies have demonstrated that iNPH frequently coexists with these neurocognitive and psychiatric disorders, promoting a further exploration of the potential associations that were not previously elucidated (Yoshino et al, 2020;Israelsson et al, 2016;Kito et al, 2009). The presence of comorbid PD or PD dementia has been shown to exacerbate the clinical course of iNPH, underscoring the need to unravel the potential association between iNPH and PD for more informed treatment planning (Sakurai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A widely accepted consensus posits that the enlargement of brain ventricles in iNPH is associated with compromised CSF homeostasis (Wang et al, 2020). Additionally, previous studies have demonstrated that iNPH frequently coexists with these neurocognitive and psychiatric disorders, promoting a further exploration of the potential associations that were not previously elucidated (Yoshino et al, 2020;Israelsson et al, 2016;Kito et al, 2009). The presence of comorbid PD or PD dementia has been shown to exacerbate the clinical course of iNPH, underscoring the need to unravel the potential association between iNPH and PD for more informed treatment planning (Sakurai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, iNPH commonly presents concomitantly with psychiatric disorders in elderly individuals, including depression, anxiety, and schizophrenia (SCZ) (Israelsson et al., 2016 ; Kito et al., 2009 ; Yoshino et al., 2020 ). A more frequent possibility of iNPH in older patients with SCZ than in the general population has been reported (Yoshino et al., 2020 ). Moreover, a prior investigation demonstrated that iNPH patients were more prone to have a positive depression screen and a history of psychiatric disorders (Ghaffari‐Rafi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathomechanisms underlying IIH and iNPH are not fully understood, and many reports suggest that a combination of several factors is involved ( 1 , 10 ). Venous sinus stenosis, metabolic disorders, obesity-induced elevated inflammatory cytokines, and impaired venous return are reported to be risk factors for IIH ( 1 ), while cerebrovascular disease and schizophrenia are reported to be risk factors for iNPH ( 4 , 11 ). The involvement of CSF efflux mechanisms, such as the glymphatic system ( 12 ), has been proposed as a common pathology in both diseases ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%